Enhancement of the anthocyanin contents of Caladium leaves and petioles via metabolic engineering with co-overexpression of AtPAP1 and ZmLc transcription factors - Yang, Ximeng; Li, Airong; Xia, Jing; Huang, Yan; Lu, Xin; Guo, Gangyu; Sui, Shunzhao (Frontiers in Plant Science, 2023)
Metabolic engineering of anthocyanin synthesis is an active research area for pigment breeding. Caladium bicolor is a desirable anthocyanin metabolic engineering receptor, with its abundant leaf color and stable genetic transformation system. Additionally, the effects of two transcription factors, AtPAP1 and ZmLc, on anthocyanin production remain to be explored. We transformed C. bicolor with AtPAP1 and ZmLc and successfully obtained transgenic plants. We then used a combination of metabolome, transcriptome, WGCNA and PPI co-expression analyses to identify differentially expressed anthocyanin components and transcripts between wild-type and transgenic lines. Cyanidin-3-O-glucoside, cyanidin-3-O-rutinoside and peonidin-3-O-rutinoside are the main components of anthocyanins in C. bicolor. Exogenous introduction of AtPAP1 and ZmLc resulted in significant changes in pelargonidins, particularly pelargonidin-3-O-glucoside and pelargonidin-3-O-rutinoside in C. bicolor. Furthermore, 5 MYB-TFs, 9 structural genes, and 5 transporters were found to be closely associated with anthocyanin synthesis and transport in C. bicolor. In this study, a network regulatory model of AtPAP1 and ZmLc in the regulation of anthocyanin biosynthesis and transport in C. bicolor was proposed, which provides insights into the underlying regulatory mechanisms of AtPAP1 and ZmLc, and lays a foundation for the precise regulation of anthocyanin metabolism and biosynthesis.